2018
DOI: 10.1002/aenm.201802158
|View full text |Cite
|
Sign up to set email alerts
|

Superwetting Monolithic Hollow‐Carbon‐Nanotubes Aerogels with Hierarchically Nanoporous Structure for Efficient Solar Steam Generation

Abstract: hydrogen, [2] solar power plants, [3] photovoltaic cells, [4] photocatalysis, [5] and water desalination, [6] the photothermal materials based solar water evaporation is one of the most promising approaches for harvesting and conversion of solar energy. Solar vapor generation, more specifically, is a surface water evaporation process in which the light is absorbed and converted to heat energy by photothermal materials to generate vapor. Compared with the common water evaporation by solar radiation as heat sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
237
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 394 publications
(238 citation statements)
references
References 39 publications
(68 reference statements)
1
237
0
Order By: Relevance
“…Beside an ideal solar absorbing performance, the vertically aligned array of BNF flocking board possesses a unique water self‐supply ability simultaneously, which makes the liquid transport rapidly due to the wicking effect . The surface wettability has been considered as one of the important factors for water transportation during evaporation . The images (Figure S2, Supporting Information) captured by a high‐speed camera showed that the water droplet spreads and wicks quickly after it touches the BNF flocking board surface.…”
Section: Resultsmentioning
confidence: 99%
“…Beside an ideal solar absorbing performance, the vertically aligned array of BNF flocking board possesses a unique water self‐supply ability simultaneously, which makes the liquid transport rapidly due to the wicking effect . The surface wettability has been considered as one of the important factors for water transportation during evaporation . The images (Figure S2, Supporting Information) captured by a high‐speed camera showed that the water droplet spreads and wicks quickly after it touches the BNF flocking board surface.…”
Section: Resultsmentioning
confidence: 99%
“…To further clarify the surface chemical properties of BFT, X‐ray photoelectron spectroscopy (XPS) was carried out (Figure d). With a carbon concentration of 76.00 %, BFT gave a C 1s spectra that can be deconvoluted into two peaks (Figure e), which can be attributed to aliphatic carbon (285.0 eV) and ether linkages or alcohol groups (285.4 eV) . The oxygen concentration was 23.14 % and the O 1s spectrum could be deconvoluted into two peaks (Figure f), which, were assigned to alumina (531.1 eV) and silica (532.5 eV).…”
Section: Figurementioning
confidence: 99%
“…The severe environmental pollution issues as well as energy crisis has aroused the emphases for development of clean and renewable energy resource . Among a variety of sustainable energy resources, solar energy has long been considered as green and unexhausted energy which has been the hot points of various kinds of sustainable energy . As a kind of solar energy utilization manner, in recent years, the use of photothermal materials for solar steam generation has received considerable attention both in academy and industry due to their high evaporation rate along with high solar energy conversion efficiency by comparison with that of common bulk water vaporization .…”
Section: Introductionmentioning
confidence: 99%